Avaliação do serviço de disseminação seletiva de informações do Centro de Informações Nucleares em relação á precisão, recuperação e novidade - Soares, Selma Chi Barreiro (1979)
The performance of the SDI service of the Nuclear Information Center (CIN) is presented. The measures used were precision, recall and novelty. The general conclusion is that the system is operating with a high precision (86.1%); but its capability for retrieving relevant documents is low (26.7%). The major source of precision failures was defective search logic and the major source of recall fail ures was lack of specific terms in the entry vocabulary. Concerning the novelty ratio, it was concluded that the overall ratio of the system is 82% and among the documents considered as new by the users, 80% were highy relevant.